Household food insecurity and coping strategies among pensioners in Jimma Town, South West Ethiopia - Misgana Asesefa Kisi; Dessalegn Tamiru; Melese Sinaga Teshome; Meseret Tamiru; Garumma Tolu Feyissa (BMC, 2018)
Abstract Background Ethiopia is currently facing new challenges related to food insecurity among the urban poor. Pensioners are segments of the population with reduced income and working capacity because of advancement of age and other related problems. There is no empirical evidence on Jimma Town pensioner's household food insecurity and coping strategies. Methods A cross-sectional study was conducted among households in Jimma Town living on an income obtained from a pension from March 01-28, 2017. Data were collected from 399 randomly selected participants. Data were entered into EPi-Data version 3.1 and analyzed using SPSS Version 20.0. Variables with p ≤ 0.25 in the bivariate analyses were entered into a multivariable regression model to control for confounding variables. Results Nearly, 83.5% of households were food insecure. The odds of food insecurity among households with heads attending secondary school and above was 78% lower when compared to that of households with uneducated household heads (AOR = 0.22, 95% CI: 0.97 to 0.49). The odds of food insecurity among households headed by merchants was 91% lower when compared to that of households headed by guards (AOR = 0.09, 95% CI: 0.03, 0.29). Food insecure households were using coping strategies such as changing consumption patterns (44%), eating inexpensive foods (72.4%), reducing meal frequency (62.4%) and selling household assets, such as household food utensils (30.8%). The odds of food insecurity among households having large family size (≥ 7) was 3.74 times higher when compared to that of households with family size less than three (AOR = 3.74(1.27, 10.99). Conclusions Household food insecurity was associated with having households headed by uneducated, widowed and guard household heads and having large family size. Food insecure households used both consumption and asset-based coping strategies such as eating less preferred, lower quality or less expensive foods and receiving donation from relatives or friends. Government policies should consider revising the current social protection scheme for pensioners. Special attention should be given to widow pensioners and pensioners with low educational status and with large family sizes.